LAW ENFORCEMENT THROUGH ‘LUDRUK’ AND CULTURAL ADVANCEMENT - Tomy Michael (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
The increasingly rampant corruption in Indonesia requires creative countermeasures. One way is to assimilate the law with the local culture of a region. The local culture concerned is ludruk. Ludruk, as one of Javanese traditional art performances, is admired by its fans or supporters in East Java and can be used as a means to proclaim everything about corruption. It can be concluded that the assimilation of the law with the local culture of a region is not contrary to the law but it is becoming a media in eradicating corruption. Anti-corruption teaching can be delivered through ludruk as long as it remains in accordance with the nature of ludruk itself.